The Specific Features of Baltic, Tocharian and Sanskrit Verbs - Chomičenkienė, Aleta (Acta Orientalia Vilnensia, 2001)
A number of both synchronic and diachronic studies devoted to the analysis of the verb of the Tocharian language have appeared lately; they present not only the systems of tense, mood and voice and respective endings, but also emphasise the archaic features of the Tocharian verb that have structural parallels in other Indo-European languages. In the opinion of many researchers, the system of the Tocharian verb preserved quite a number of archaisms. On the other hand, one can find many innovations that influenced the system of the Tocharian verb already during the period of the independent existence of the language; appearance of new tenses (e.g., Imperfect) and new suffixes -tk, -sk- should be mentioned among them.According to D. Adams, the system of Proto-Tocharian verb consists of the following tenses: Present, Preterite; moods: Subjunctive, Optative, and Imperative; Tocharian preserved both voices: Active and Mediopassive, and three moods: Conjunctive, Optative and Imperative. Tocharian verbs are divided into 11 classes.The reflexes of Baltic, Tocharian and Sanskrit verbs (of the rauna//rauja type) can be classified according to the root affix. They are as follows:a) a group of the zero affix thematic verbs: Toch B.lyew- (‘sends away, weakens’ (class II-III), cf. Lith. liauna//liauja, and Toch. A rwā- (‘pulls off’ (class V), related to Lith. rauna//rauja ‘pills’; Skr. gavate (class I) ‘sounds’, related to Lith. gaunal/gauja ; Skr. yuvati//yuvate, ‘unites’ compared to Lith. jauna//jauja ‘lumps together’; Skr. mīvati ‘moves’, related to Lith. mauna//mauja; Skr. ržhivati ‘spits’, cc. Lith. spjauna//spjauja; Skr. plavate ‘floats, blows as the wind’ and Lith. plauna//plauja;b) a group of the zero affix athematic verbs (class II): Skr. youti ‘lumps together’, related to Lith. jauna//jouja; Skr. rauti ‘bellow’ and Lith. rauna//rauja;c) a group of athematic verbs with suffixes -nā-/-nī (class IX), cf. yunāti, yunīte ‘unites’ related jauna//jauja; Skr. Ā lunati, lunite ‘divides’ and Lith. liauti//liauja ; Skr. P. Ā. punāti, punīte ‘makes clean’ and Lith. pjauna//pjauja;d) -tk- suffix verbs: Toch A lotk, B klautk- ’become, return’, related to Lith. kliauna//kliauja ‘gets caught, turns’;e) verbs with the determinative -p- (lE *bh): Toch A krop-, B kraup- ’pile up, heap up’( class IV,V), related to Lith. kraunal/ krauja ;f) verbs with the determinative -t-: Toch. A kot-, Toch. B kaut- ‘to split, to tear’, related to Lith. kauno//kauja.Baltic, Tocharian and Sanskrit reflexes underwent individual changes after the separation of the languages. Semantic changes are greater in the Sanskrit verb system.